The hunt for Osama bin Laden - Bodden, Valerie (Turning points (Creative Education, Inc. (Mankato, Minn.)), 2020)
Examines the events leading up to and surrounding the assassination of Osama bin Laden, discussing how bin Laden evolved from millionaire's son, to jihadist, to the most wanted criminal in the world. Describes the events leading up to his killing and the aftereffects, including renewed calls by Muslim extremists for attacks on America and the West. Includes photographs, a timeline, a glossary, and resources for further reading.